Forecasting the streamflow changes trend by sdsm-ihacres model at Sg Jeram, Pahang - Muhamad Syarifuddin, Yem (2018)
Greenhouse gases (GHGs) is a natural phenomenon to keep the Earth warm. Greenhouse effect plays their role when GHGs absorb heat from the ground. Nowadays, less heat escapes from the space and more re-emitted heat trapped by GHGs which rapid increasing the global temperature. Carbon dioxide (CO2) is the major contributor of abnormally greenhouse GHGs (Sumner,2015). The higher the amount of those gases in the atmosphere, the higher the local temperature of specific location. The local temperature is directly related with rainfall-runoff relationship. In general, the water runoff increases when the amount of precipitation increases. On the other hand, the water runoff decreases when the air temperature increases. Nowadays, the fluctuation of rainfall, temperature and streamflow becomes unexpected compared to historical recorded data. Some places on Earth receive too much water and some receive very little amount of water to sustain the economy and the people’s living. So, it is vital to assist water reservoir management by evaluating future streamflow pattern especially in Malaysia where the natural disasters such as droughts and flood cannot be expected. In this study, historical rainfall and temperature data at Sg. Jeram Bungor, Pahang were analysed in Statistical Downscaling (SDSM) model to generate future rainfall and temperature trend. Then, the results from the SDSM model were analysed in Identification of unit Hydrographs And Component flows from Rainfall, Evapotranspiration and Streamflow (IHACRES) to generate future streamflow pattern at Jeram Bungor.